2015
DOI: 10.12932/ap0498.33.2.2015
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of childhood atopic dermatitis: a retrospective cohort study

Abstract: Half of AD had completely disappeared at preschool age. Good prognosis was mostly determined by early onset AD and mild severity. Late onset, family history of atopy and increased serum IgE level are associated with respiratory allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 20 publications
(35 reference statements)
3
36
1
2
Order By: Relevance
“…Most of the infants had mild to moderate severity; however, the EASI score increased with age, reaching >30% of that of severe adult patients. As in previous studies, the severity was either mild or moderate in >80% of the infants and children,1518 whereas a higher percentage (25%-31%) of patients in their adulthood had severe AD 734. Some other studies, however, showed contradictory data, with only 1.7% of adult patients having severe AD 19.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Most of the infants had mild to moderate severity; however, the EASI score increased with age, reaching >30% of that of severe adult patients. As in previous studies, the severity was either mild or moderate in >80% of the infants and children,1518 whereas a higher percentage (25%-31%) of patients in their adulthood had severe AD 734. Some other studies, however, showed contradictory data, with only 1.7% of adult patients having severe AD 19.…”
Section: Discussionmentioning
confidence: 49%
“…Family history, one of the major criteria in the diagnosis of AD, is known to be an important risk factor for AD. Studies from Western countries have found a positive family history of atopy in 53%-80% of patients 1516. In a recent study in Korean children with AD, about 40% had a family history,17 whereas a few others have shown a positive family history in 28% and 47.8% 1518.…”
Section: Discussionmentioning
confidence: 96%
“…Between 10 and 20% of children in Asia suffer from atopic dermatitis and up to 10% of these are severe . The prevalence of food allergy in most Asian populations is generally low, and egg is the commonest food allergen in the majority of Asian countries .…”
Section: Summary Of Existing Evidencementioning
confidence: 99%
“…Similarly, no significant difference was found in terms of sex in children with acute and chronic urticaria by Chang et al (10), in children with acute urticaria who presented to emergency department by Liu et al (11), or in children with food-induced urticaria by Wananukul et al (12). However, urticaria is observed more frequently in adult women compared with adult men (3).…”
Section: Discussionmentioning
confidence: 99%
“…The success of specifying triggering factors in urticaria ranges between 21% and 83% in different studies (10)(11)(12)(13)(14)(15)(16). In our study, we found no factors that could lead to urticaria in approximately one fifth of the children with acute urticaria, and in approximately half of the children with chronic urticaria.…”
Section: Discussionmentioning
confidence: 99%